A Study On The Behavioural Patterns Of International Tourists At Perhentian Island - Iqbal Hussain, Hafezali (2007)
This study examines the behavioural patterns of international tourists at Perhentian island which is a popular tourist destination located on the East Coast of the peninsular of Malaysia.